GLOBALISASI, POSTMODERNISME DAN TANTANGAN KEKINIAN SOSIOLOGI INDONESIA - Fansuri, Hamzah (The Sociology of Islam, 2012)
Sociology of Indonesia in its development to date is a study that is often unaware of the attention in academic circles. Although in the early phase of institutionalization has emerged original ideas that seeks to explore aspects of sociology rooted in cultural, historical, and social problems and political economy of Indonesian society, but the idea is then that such stagnation triggered by the political power of the New Order regime . In addition, the U.S. dominance in the context of post-World War II when it's against the developing countries or countries of the former colonial influence is so strong to the realm of science in which scientific products become more mainstream in social science such as theory-paradigm of modernization theory and Parsonian functionalism and even still continues to this day, so reap the methodological debate. Meanwhile, globalization as a contemporary phenomenon that can not be avoided it has become a space for the emergence of various alternative approaches to address the scientific challenges of the times in which the boundaries between regions ranging from the regional to the global scope are blurred, as well as theoretical, paradigmatic and conceptual that has shaken confidence in the classical sociology itself, such as the concept of society. So is the epistemology of postmodernism and post-structuralism through their thinkers, who were born as the antithesis of the unhappiness of the modernization project, the more enriching the treasure of the sociology of science by offering new approaches to deconstructive, sided with the Others and brought the idea of liberation. Therefore, the sociology of Indonesia is a science projects that continue to face the challenges of the times, since the post-World War II marked the superiority of the U.S. social sciences until it became stronger when globalization threatens human survival and therefore requires a new science device that remains refers to the special characteristics that exist in Indonesian society. Kata Kunci: Globalisasi, Posmodernisme, Sosiologi Indonesia